Psychological and pedagogical basis for the formation of elements of design thinking in the classroom high school technology (Pedagogy of Higher and Secondary Education, 2012)
Dubovа N. Psychological and pedagogical basis for the formation of elements of design thinking in the classroom high school technology.In the article considers and analyzes the complex psychological and pedagogical conditions of the elements of design thinking senior pupils technologies.
Keywords: design thinking; art education; technology teacher; high school students; art and design activities